Celiac disease in children with urolithiasis - Menekse, Engin; Selimoglu, Mukadder Ayse; Temel, Ismail; Tabel, Yilmaz; Gurgoze, Metin (Turkish J Pediatrics, 2012)
There are a few studies suggesting a relationship between celiac disease (CD) and kidney disease, but no study has investigated CD in patients with urolithiasis. In this study, we aimed to determine the prevalence of CD in infants and children with urolithiasis. One hundred and eighty-seven infants and children (4 months-17 years) with urolithiasis, and 278 age- and sex-matched healthy children were included. CD was screened using tissue transglutaminase (tTG) immunoglobulin (Ig) A. Seropositive cases, whose parents gave consent, underwent upper gastrointestinal system endoscopy for duodenal biopsy. Seven (3.7%) among those with urolithiasis and one (0.3%) among controls were positive for tTG IgA (p=0.008). Six of the urolithiasis group and one from the control group underwent upper gastrointestinal endoscopy. Intestinal biopsy revealed Marsh-Oberhuber type 1 intestinal lesions in two children. The other five had normal histology. Biopsy-proven CD was detected in two (1%) children with urolithiasis. The prevalence of biopsy-proven CD among all cases was 0.4%. When children were evaluated with respect to age factor, it was found that seropositivity in children younger and older than two years was not different (4% vs. 3.6%; p=0.880). In this first study investigating CD prevalence in children with urolithiasis, we found a higher seropositivity for CD in children with urolithiasis compared to controls, but in terms of biopsy-proven CD, no difference was found.
Keywords: celiac disease; children; urolithiasis